El envejecimiento de la población en Honduras - Castellón, Raúl Hernández; Aguilar, Francisco; Baca, Hector Y; Borjas, Ulda R; Borjas, Claudio A; Borjas, Noemí; Monje, Digna América; Ponce, Victoria; García, Nelson Raudales; Molina, Sonia Salguero (Población y Desarrollo - Argonautas y Caminantes, 2012)
DOI: http://dx.doi.org/10.5377/pdac.v2i0.827 Población y Desarrollo - Argonautas y Caminantes Vol.2 2004 35-57